New Glutamine-Containing Substrates for the Assay of Cysteine Peptidases From the C1 Papain Family - Filippova, Irina Y.; Dvoryakova, Elena A.; Sokolenko, Nikolay I.; Simonyan, Tatiana R.; Tereshchenkova, Valeriia F.; Zhiganov, Nikita I.; Dunaevsky, Yakov E.; Belozersky, Mikhail A.; Oppert, Brenda; Elpidina, Elena N. (Frontiers in Molecular Biosciences, 2020)
New substrates with glutamine in the P1-position are introduced for the assay of peptidases from the C1 papain family, with a general formula of Glp-Phe-Gln-X, where Glp is pyroglutamyl and X is pNA (p-nitroanilide) or AMC (4-amino-7-methylcoumaride). The substrates have a simple structure, and C1 cysteine peptidases of various origins cleave them with high efficiency. The main advantage of the substrates is their selectivity for cysteine peptidases of the C1 family. Peptidases of other clans, including serine trypsin-like peptidases, do not cleave glutamine-containing substrates. We demonstrate that using Glp-Phe-Gln-pNA in combination with a commercially available substrate, Z-Arg-Arg-pNA, provided differential determination of cathepsins L and B. In terms of specific activity and kinetic parameters, the proposed substrates offer improvement over the previously described alanine-containing prototypes. The efficiency and selectivity of the substrates was demonstrated by the example of chromatographic and electrophoretic analysis of a multi-enzyme digestive complex of stored product pests from the Tenebrionidae family.